Process evaluation of an intervention to improve access to injectable contraceptive services through patent medicine vendors in Nigeria: a mixed methods study (2021)
Background: The low utilisation of modern contraceptives in many low- and middle-income countries remains a challenge. Patent medicine vendors (PMVs) that operate in the informal health sector, have the potential to address this challenge. Between 2015 and 2018, the Population Council, in collaboration with the Federal and State Ministries of Health and the Pharmacy Council of Nigeria, trained PMVs in six states to deliver injectable contraceptive services. Outcome evaluation demonstrated increased client uptake of injectable contraceptive services; however, there is limited information on how and why the intervention influenced outcomes. This study was conducted to elucidate the processes and mechanism through which the previous intervention influenced women’s utilisation of injectable contraceptive services. Methods: The study utilised a mixed methods, convergent parallel design guided by the UK Medical Research Council framework. Quantitative data were obtained from 140 trained PMVs and 145 of their clients in three states and 27 in-depth interviews were conducted among relevant stakeholders. The quantitative data were analysed descriptively, while the qualitative data were analysed thematically. Results: The results revealed that even after the completion of the PMV study which had a time-bound government waiver for injectable contraceptive service provision by PMVs, they continued to stock and provide injectables in response to the needs of their clients contrary to the current legislation which prohibits this. The causal mechanism that influenced women’s utilisation of injectable contraceptives were the initial training that the PMV received; the favourable regulatory environment as demonstrated in the approval provided by government for PMVs to provide injectable contraceptives for the duration of the study; and the satisfaction and the confidence the female clients had developed in the ability of the PMVs to serve them. However, there were gaps with regards to the consistent supply of quality injectable contraceptive commodities and in PMVs use of job aids. Referral and linkages to government or private-owned facilities were also sub-optimal. Conclusion: PMVs continue to play important roles in family planning service provision; this underscores the need to formalize and scale-up this intervention to aid their integral roles coupled with multi-faceted initiatives to enhance the quality of their services.